2014
DOI: 10.5539/esr.v3n2p27
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis Using Aeromagnetic Data: Case Study of Parts of Southern Bida Basin, Nigeria and the Surrounding Basement Rocks

Abstract: Structural analysis using aeromagnetic data over parts of southern Bida (Nupe) basin, Nigeria and the surrounding basement rocks was carried out to highlight linear structures and infer the effects of such features on the tectonic events in the survey area. The basin consists of the basal Lokoja Formation, overlain by the Patti Formation and capped by the Agbaja Formation. The basal Lokoja Formation is a sequence of matrix supported conglomerates and sandstones overlying the Pre-Cambrian to lower Palaeozoic ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…Present are the minor N-S fractures which are attributed to brittle deformation and the twin conjugate sets of NE-SW and NW-SE trends, produced by transcurrent movements [38]. The age relationships of the conjugate fracture sets cannot be easily resolved from their relative dispositions on the map, but it has been established that NW-SE trending lineaments are analogous to the predominant trend of the Bida Basin [35]. The structural framework of the Nigerian Basement Complex is dominated by the NE-SW lineaments [35,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Present are the minor N-S fractures which are attributed to brittle deformation and the twin conjugate sets of NE-SW and NW-SE trends, produced by transcurrent movements [38]. The age relationships of the conjugate fracture sets cannot be easily resolved from their relative dispositions on the map, but it has been established that NW-SE trending lineaments are analogous to the predominant trend of the Bida Basin [35]. The structural framework of the Nigerian Basement Complex is dominated by the NE-SW lineaments [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…This deformation event is closely related to the formation of the schist belts and mylonites in the region. [35] have attributed NE-SW trend to the landward extension of the Chain and Romanche Fracture Zones from the Atlantic Ocean [36].…”
Section: Lineaments and Lineament Density Mapsmentioning
confidence: 99%
“…The method is therefore well established in its use in inferring depth to magnetic sources (Bhattacharya, 1966;Spector and Grant, 1970). Previous studies on the analysis of aeromagnetic data have been carried out in Bida Basin by Bemsen et al (2013), Obi et al(2015), Megwara and Udensi (2014), and Nwankwo et…”
Section: Introductionmentioning
confidence: 99%
“…al. (2008).Similarly, Megwara and Udensi (2014) carried out a structural analysis of the aeromagnetic data over the study area using the Werner and Euler deconvolution. The analyses which was carried out along profiles revealed depths to the magnetic sources of the range 0.01 km to 0.51 km with an average value of 0.128 km.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Ofor et al (2014) carried out a study of Pategi and Egbako areas of the lower Bida basin and revealed two prominent layers; with average values of 0.59km and 3.1km respectively. Megwara, and Udensi (2014) also carried out structural analysis using aeromagnetic data over parts of southern Bida basin and the surrounding basement rocks and found the depth to be within the range of 0.01km to 0.51km with an average value of 0.128km. Ojo and Ajakaiye (1989) delineated the presence of a positive gravity residual centre in the basin.…”
mentioning
confidence: 99%